Design and testing of a parabolic solar concentrator with automatic tracking system - Youcef Mebarki; Abdelhakim Belkaid (Revue des Énergies Renouvelables, 2024)
The undertaken work revolves around an experimental investigation into harnessing solar energy and its conversion into thermal energy through the utilization of a parabolic concentrator. Ensuring optimal orientation concerning solar radiation is facilitated by an automatic tracking system. The prototype employed for testing primarily consists of a solar reflector, shaped as a parabola to efficiently reflect solar radiation, and an absorber comprising a coiled copper tube, designated as the focal point for concentrating the sun's rays. The attained results are significant, with temperatures surpassing 380°C recorded on the absorber's surface.